2012
DOI: 10.2298/mpns1206247p
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-level laser therapy on xerostomia (mouth dryness)

Abstract: The current literature suggests that low-level laser therapy can be safely and effectively used as an advanced treatment modality for reduction of xerostomia. Further in vivo, in vitro and clinical studies using different irradiation parameters are suggested to determine the best laser parameters to be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Although there are many available treatment modalities to enhance salivary flow, the therapy often remains unsatisfactory. PBM has been extensively used as a new advantageous tool for the reduction of xerostomia …”
Section: Role Of Photobiomodulation In Oral Medicinementioning
confidence: 99%
“…Although there are many available treatment modalities to enhance salivary flow, the therapy often remains unsatisfactory. PBM has been extensively used as a new advantageous tool for the reduction of xerostomia …”
Section: Role Of Photobiomodulation In Oral Medicinementioning
confidence: 99%
“…Although numerous published studies have focused on the role of RAGE and its ligands in diabetes, little is known about the expression of AGE, HMGB1 and RAGE in diabetic submandibular glands (SMGs), as well as the effects of diabetes on apoptosis and proliferation markers in that tissue. Furthermore, in the last decade, low-power laser therapy (LPLI) has been applied clinically for the treatment of hyposalivation [1720]. Our group previously reported that LPLI increases salivary flow of irradiated rat salivary glands [21] and improves the antioxidant enzyme activities of superoxide dismutase and catalase in SMGs of diabetic rats [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one study stated that the effects of LLLT on salivary glands are not only motivating, but also restore the glandular response to the same quantity of applied laser therapy (26) . Another study found that LLLT could markedly increase salivary excretion and ameliorate antimicrobial features of secreted saliva (elevated level of sIgA) (27) .…”
Section: Discussionmentioning
confidence: 99%